Beginning Nurses' Perceptions of Ethical Leadership in the Shadow of Mid Staffs. (3rd July 2017) - Mastracci, Sharon
Abstract : Prior research has established the role of ethical leadership in promoting positive workplace outcomes. Nevertheless, in the wake of scandal, what is the perception of ethical leadership by new entrants into the scandalized profession? Can ethical leadership still promote positive behavior? Path analysis using survey data from 159 beginning nurses reveals the presence of ethical leadership after the worst tragedy in the history of England's National Health Service (NHS). Furthermore, nurses respond to perceived ethical leadership with increased helping behaviors and decreased experience of burnout. This confirms and extends previous research linking ethical leadership to job satisfaction, organizational commitment, and job engagement, and to an increased likelihood to report unethical practice. Survey respondents entered nursing at a time when the profession was highly scrutinized in the shadow of crisis at the Mid Staffordshire NHS Foundation Trust.